Fall armyworm threat in Africa - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2018)
Biorisk Management Facility (BIMAF): An innovative multi-stakeholder platform that studies the links between climate change and biotic stresses - Fall armyworm.